FPGA Based Low Area Motion Estimation with BISCD Architecture (International Journal of Engineering and Computer Science, 2014)
The Motion Estimation Computing Array (MECA) is used in Video Encoding applications to calculate the best motion between the current frame and reference frames. The MECA is in decoding application occupies large amount of area and timing penalty. By introducing the concept of Built-in Self test technique the area overhead is increased in less amount of area. In this Paper the Built-in Self test Technique (BIST) is included in the MECA and in each of Processing Element in MECA is tested using residue codes .the quotient and remainder was cross checked across the processing element and test code generator. Further the residue and quotient code complex operation is replaced with the simple Boolean logic division operation in order to reduce the area of the circuit. Thus by introducing the BIST Concept the testing is done internally without Connecting outside testing Requirements. So the area required is also reduces. And in this Paper the Errors in MECA are Calculated and the Concept of Diagnoses i.e. Self Detect and Self Repair Concepts are introduced.